RADI-42. ASSOCIATION BETWEEN TUMOR LOCATION AND TOXICITY OUTCOMES AFTER STEREOTACTIC RADIOSURGERY FOR BRAIN METASTASES. (12th August 2019) - Wang, Boya; Kaidar-Person, Orit; Sasaki-Adams, Deanna; Jaikumar, Sivakumar; Ewend, Matthew; Nakamura, Zev; Chen, Ronald; Zagar, Timothy; Tepper, Joel; Marks, Lawrence; Khagi, Simon; Shen, Colette
Abstract: OBJECTIVE: The toxicities associated with stereotactic radiosurgery (SRS) are important factors when considering treatment options and supportive management for patients with brain metastases. We assessed the association between brain metastasis location and rates of toxicity after SRS. METHODS: We conducted a retrospective single-institution review of 170 patients treated with SRS for brain metastases from 2008–2016 with median follow-up of 8.6 months. Typical SRS doses were 18-20Gy in 1 fraction (lesions < 2cm), 18-21Gy in 3 fractions (lesions 2-3cm), and 25-30Gy in 5 fractions (lesions >3cm). Toxicity measures evaluated included radiation necrosis, seizure, and dexamethasone requirement. RESULTS: A total of 221 lesions were treated among frontal (29%), cerebellar (23%), parietal (16%), temporal (15%), occipital (14%), and other (brainstem, thalamus, basal ganglia) (4%) regions. The rate of SRS-related radionecrosis was 4% for all patients and significantly correlated with metastasis volume (increasing from 1% to 7% for lesions ≤1cm 3 to >3cm 3 ) and prior whole brain radiotherapy (WBRT) but not with metastasis location or prior resection on multi-variable analysis (P< 0.05). Post-SRS seizure occurred in 9% of all patients but was significantly higher for primary motor cortex and sensory cortex lesions, associated with 52% and 33% seizure rates, respectively (P< 0.05). Of patients who initially presented with seizure and were on anti-epileptic medication during SRS, 53% had no further seizures, while 47% did have post-SRS seizures, nearly all with motor cortex lesions. Only 5% of patients had new-onset seizure after SRS, related to lesion hemorrhage or motor cortex location. Dexamethasone use >3 months post-SRS was higher for motor strip lesions. CONCLUSION: Brain metastasis location in the primary motor cortex was associated with higher rates of post-SRS seizure, including new-onset seizures and breakthrough seizures on anti-epileptic medication during SRS. Rates of radionecrosis were associated with lesion volume and prior WBRT but not with metastasis location.